Metode pembiasaan dalam membangun kemandirian anak autisme spectrum disorder di SD Muhammadiyah Alam Surya Mentari - Anggita Dea Apriliasari; Galih Fajar Fadhilah (Nur Science Institute, 2024)
Independence is an independent character trait instilled and developed in children from an early age; this habit will build a strong personality. The problem is that children with ASD are too dependent on special assistant teachers when they are going to carry out an activity at school. The method used by special assistant teachers is repeated, a regular habituation to help build children with ASD's independence. The purpose of this study is to describe the application of habituation methods to build independence in children with ASD at SD Muhammadiyah Alam Surya Mentari. This study uses a descriptive qualitative method. The informants in this study were two special assistant teachers selected through purposive sampling. Data collection techniques used interviews and observations. The data validity method is a triangulation technique. Data analysis uses data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the habituation method for building independence in children with ASD at SD Muhammadiyah Alam Surya Mentari is divided into preparation for the habituation method, its implementation, and its evaluation. With the implementation of the habituation method, children with ASD can engage in activities effectively in areas of emotional independence, behavior, and values.